Acid conditioning of root surfaces that are periodontally affected as an adjunct to periodontal therapy: a literature review (Research, Society and Development, 2020)
As an adjunct to this treatment, the acid conditioning of these surfaces was introduced with the purpose of helping to make the region more propitious to the reestablishment of previously injured tissues. The objective of this review is to evaluate the main benefits of citric acid and ethylenediaminetetraacetic acid (EDTA) solutions in their different concentrations as an adjuvant to the treatment of root surfaces in Periodontics. To carry out this study, the following databases were consulted: Virtual Health Library (VHL), Medical Publications (PubMed), Google Scholar, Medline and the Scientific Electronic Library online (SCIELO). To carry out this search, the Health Science Descriptors (DECS) were used: Periodontal diseases, Citric acid, Edetic acid and Periodontics. It is known then that chemical conditioning of the root surfaces is of extreme importance in the periodontal treatment of periodontally compromised root surfaces, where the concentrations of 1% and 25% of citric acid and 24% of ethylenediaminetetraacetic acid (EDTA), according to the Studies, have proven to be the most effective in their different commercial presentations. So it is concluded that the adjunctive treatment with acid attack contributes to: removal of the smear layer, exposure of the collagen fibers network, effective adhesion of blood elements to the root surface, and especially respect to the periodontal tissues previously damaged by the presence of periodontal disease, Thus allowing the reestablishment of the anatomical position of the tissues.